Demographic and Personal Factors that Encourage Iraqi People to Undergo Plastic Surgery - Noaman, Aqeel Abbas; Abbas, Mounaem Akram; Dhahi, Naser Kareem (International Journal of Psychosocial Rehabilitation, 2020)
BackgroundThe body's images are defined as the mental image of one body, where it is formed by perception, emotions and physical sensations, as well as all the physiological and emotional changes that an individual goes through. In these circumstances, all social institutions and agents play a crucial role in creating this image.AIMThe study aims to identify the demographic factors of the individual that increase the rate of plastic surgery and determine the region and the type of plastic procedure more communist for cosmetic surgery and know the personal reasons of the individual leading to plastic surgery. MethodsAn analytical-cross sectional study was conducted on (79) Iraqi people, ages 18-64 years old, all of whom underwent one or more cosmetic surgery in various Iraqi hospitals and were randomly selected between January and February 2019. A questionnaire was prepared that included (age group, gender, employment status, educational level, place of residence, type and location of surgery, and personal reasons for plastic surgery). The data was entered for analysis using the Social Science Statistical Package Program (Version 21.0). The Chi-square test and t-test were used to indicate the statistical differences of the variables studied where the value (< 0.05) was considered as a minimum for statistical indication. Results People who accepted plastic surgery had an mean age of 29.47 years, most of them (65.8%) were females, and more than half were employees (53.2%) and well educated (55.7%). Majority of them (86.1%) were live in urbans. Significantly the head area (face) recorded the highest percentage (59.5%) for plastic surgeries. It was noted that rhinoplasty significantly recorded the highest percentage (35.4%) among other plastic surgeries, the study showed that Finally, the study showed that (73.4%) of people who have undergone plastic surgery is to improve the appearance to get more beautiful. ConclusionsThe results of the current study have concluded that females are more likely to perform plastic surgery, a job factor and a university education increase the chances of attracting plastic surgery, more than a third of whom have undergone rhinoplasty, also improving the appearance to get more beautiful was one of the most common reasons for the plastic surgeries.